Adipokines, Hepatokines and Myokines: Focus on Their Role and Molecular Mechanisms in Adipose Tissue Inflammation - Ren, Yakun; Zhao, Hao; Yin, Chunyan; Lan, Xi; Wu, Litao; Du, Xiaojuan; Griffiths, Helen R.; Gao, Dan (Frontiers in Endocrinology, 2022)
A chronic low-grade inflammation in adipose tissue is a hallmark of obesity and contributes to various metabolic disorders such as type 2 diabetes and cardiovascular diseases. Adipose tissue inflammation is characterized by macrophage infiltration and activation of inflammatory pathways mediated by NF-κB, JNK and NLRP3 inflammasome. Adipokines, hepatokines and myokines are proteins secreted from adipose tissue, liver and skeletal muscle that exert regulatory roles in adipose tissue inflammation via endocrine, paracrine or autocrine pathways. For example, obesity is associated with elevated levels of pro-inflammatory adipokines (e.g. leptin, resistin, chemerin, progranulin, RBP4, WISP1, FABP4, PAI-1, Follistatin-like1, MCP-1, SPARC, and SPARCL1) and reduced levels of anti-inflammatory adipokines such as adiponectin, omentin, ZAG, SFRP5, CTRP3, vaspin, and IL-10. Moreover, some hepatokines (Fetuin A, DPP4, FGF21, GDF15, MANF) and myokines (irisin, IL-6 and DEL-1) also play pro- or anti-inflammatory roles in adipose tissue inflammation. This review aims to provide an updated knowledge of these organokines in adipose tissue inflammation and related metabolic abnormalities and highlights the underlying molecular mechanisms and clinical significance. Understanding the role and mechanism of these organokines could provide novel and potential therapeutic targets for obesity-induced inflammation.